CARDIOVASCULAR AND RENAL OUTCOME OF LIVING KIDNEY DONORS ON A LONG TERM – A RETROSPECTIVE STUDY - Prashant Kumar; Akhilesh Kumar; Rahul Raj (Student's Journal of Health Research Africa, 2023)
Background: